Q&A - Ask Doubts and Get Answers
Q

Factorise the following expressions 2 x ^ 3+2 x y ^ 2+2 x z ^ 2

Q3 Factorise the following expressions

(III)

2 x^3 + 2xy^2 + 2 xz ^2

Answers (1)
Views

We have,
         2x^3 = 2 \times x \times x \times x
           2xy^2 = 2 \times x \times y \times y
           2xz^2 = 2 \times x \times z \times z
Therefore,
                2 x^3 + 2xy^2 + 2 xz ^2                                                                                                                              = (2 \times x \times x \times x) + ( 2 \times x \times y \times y) + ( 2 \times x \times z \times z)
                                = (2 \times x) [(x \times x) + (y \times y ) + (z \times z)]
                                = 2x(x^2+y^2+z^2)

Exams
Articles
Questions